2019
DOI: 10.1007/s10147-018-01387-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of S-1 monotherapy in plasma and in tears for gastric cancer patients

Abstract: Background S-1 is an oral anticancer drug composed of tegafur (FT), which is a prodrug of 5-FU, 5-chloro-2,4-dihydroxypyridine (CDHP), and potassium oxonate. Recently, some studies have been reported on watering eyes caused by S-1. However, the mechanism of watering eyes caused by S-1 is still unclear. The aim of this study was to investigate the correlation between tears and plasma concentrations of FT, 5-FU, and CDHP, which are components and active modulator of S-1. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Lacrimal tract disorders caused by S-1 are well-known adverse events. Yasui measured drug concentrations in the plasma and tears, and demonstrated that 5-FU and gimeracil concentrations exhibit a positive correlation (44). This report is expected to contribute to the establishment of preventive measures for lacrimal disorders.…”
Section: Individualized Treatment With Tdm Of 5-fu and 5-fu Prodrugsmentioning
confidence: 69%
“…Lacrimal tract disorders caused by S-1 are well-known adverse events. Yasui measured drug concentrations in the plasma and tears, and demonstrated that 5-FU and gimeracil concentrations exhibit a positive correlation (44). This report is expected to contribute to the establishment of preventive measures for lacrimal disorders.…”
Section: Individualized Treatment With Tdm Of 5-fu and 5-fu Prodrugsmentioning
confidence: 69%